Factors affecting time to brain metastases for stage 2 and 3 breast cancer patients: A large single-institutional analysis with potential screening implications. Issue 1 (7th March 2021) - Cao, Toni Q; Dixit, Karan; Santa-Maria, Cesar; Kumthekar, Priya
Abstract: Background: Breast cancer is the second most common cancer associated with brain metastases. The purpose of this study was to identify factors that impact the time to brain metastases in breast cancer patients at a single institution. Methods: Single institution retrospective study that captured all consecutive stage 2 and stage 3 breast cancer patients from 2003 to 2010. Patient characteristics analyzed included age, hormone status, HER2 receptor status, grade, stage, and time from breast cancer diagnosis to brain metastasis. Results: A total of 1218 patients were eligible for the final analysis. 849 (69.7%) patients were ER+/HER2−, 90 (7.4%) were HER2+, and 279 (22.9%) were triple-negative (TN). Overall, 74 patients (6.1%) developed brain metastases over a median follow up time of 92 months. Median times to brain metastases for HER2+, TN, and ER+/HER2− patients were 20, 26, and 57 months, respectively. Multivariate analysis demonstrated that TN disease (HR = 2.043, P = .015), grade (HR = 1.667, P = .024) and stage (HR = 3.851, P < .001) were independent risk factors for earlier brain metastases. Median times to brain metastases were 34 and 52 months for stage 3 and 2 patients, and 30, 49, and 71 months for grade 3, 2, and 1 tumors, respectively. Conclusions: This single-institutional case series demonstrates that TN breast cancer, higher stage, and higher histologic grade are associated with earlier brain metastases in multivariate analysis. Additional prospective studies are warranted to investigate the impact of brain metastases screening on survival outcome in this high-risk defined group.